Cobalt(II), Nickel(II) and Copper(II) Complexes with 3,8-Diphenyl, 4,7-diaza-2, 9-dihydroxyimino-5-methyl-3,7-decadiene - Rai, H.C.; Rai, B.K.; Singh, A.K. (Asian Journal of Chemistry, 2010)
A series of complexes having the formula [M(H2L)X2] [M = Co(II), Ni(II), X = CL-, Br-, I-, NO3- and CIO4- ] and [ML] [M = Co(II), Ni(II) and Cu(II), L = 3,8-diphenyl-4,7-diaza-2,9- dihydroxyimino-5-methyl-3,7-decadienel have been isolated from ethanolic medium. Yet another series of binuclear clusters of the type Cu2(L)X2 was obtained by reacting CuL complexes with copper (II) salts in ethanolic medium. Characterisation of the complexes has been made on the basis of elemental analysis, infrared spectra, electronic spectra, magnetic moment value, conductivity measurements and 1H NMR spectra.